The Effects of Inductive-Deductive Grammar Instruction on Students’ Grammatical Accuracy - Anita Noveria (Hasanuddin University, 2021)
The research investigated the effect of inductive-deductive teaching instruction developed from the five-step procedure by Widodo (2006). To be more specific, this research attempted to explore the significant difference between the combined inductive-deductive approach and conventional approach (deductive approach only) on the EFL students’ grammar achievement. A quasi-experimental design specifically non-equivalent group design was applied in this research in which the two experimental and control groups were compared. The subject of this research was the first-year university students of UIN Alauddin Makassar who were registered in the intensification program of English language. The instruments used were the initial and final tests of students. The results showed that after treatment, the experimental group increased by 0.36 or 36% and the control group was only 0.22 or 22%. In conclusion, there were significant achievement differences between the two groups after undergoing treatment: the combined inductive-deductive approach (experimental group) and deductive approach (control group).